EDITORIAL Role of Obesity in Breast Cancer Metastasis and Relapse - Tejo Jayadi (Berkala Ilmiah Kedokteran Duta Wacana, 2022)
The breast cancer patients survivors expected to be increased, because of better early cancer detection and better treatment. Although the survivorship should be celebrated, but there are common late effect of cancer and its treatment. So, it need to be better health care treatment provided to the survivor to give them better quality of life.